Створення, відкриття та діяльність медичної школи університету Джонза Гопкінза у 1890-х рр. - Куліченко, Алла Костянтинівна; Kulichenko, A. (Вінницький державний педагогічний університет імені Михайла Коцюбинського, 2019)
У статті висвітлено передумови створення, відкриття та особливості діяльності медичної школи Джонза Гопкінза у 1890-х рр. Встановлено, що створення медичної школи відбулося за заповітом Дж. Гопкінза та завдяки матеріальній підтримці американського жіночого руху, що боровся за одинакові умови вступу до закладів вищої освіти як для чоловіків, так і жінок. Крім того, з’ясовано, що відкриття та подальша діяльність медичної школи були ретельно сплановані – від будівель, де проходили заняття, до членів професорсько-викладацького й допоміжного складу. Вивчено позитивний організаційно-педагогічний досвід діяльності медичної школи університету Джонза Гопкінза у 1890-х рр. Ever since the Medical School was established, it differed from other American higher educational establishments. At the turn of the 19th and 20th centuries – when the medical educational paradigm in the United States was upgraded – the Hopkins model was recognized and highly recommended. It was stated by Flexner in «Medical Education in the United States and Canada: A Report to the Carnegie Foundation for the Advancement of Teaching» (1910). The article describes the preconditions of establishing, opening, and activity of Johns Hopkins University School of Medicine in the 1890s. Note that J. Hopkins’ will and the American feminist movement advocating for women’s rights, in particular, were one of the prerequisites for establishing the Medical School in question, with the School having the same admission requirements for men and women. What is more, W. Welch, W. Osler and others were among the founders of the Medical School. Once opened in 1893, the Medical School became a successful educational project of the Johns Hopkins University. Besides, the School was suggested to be the role-model higher educational establishment in the US offering a perfect combination of both theory and practice with a considerable material and technical base, highly skilled pedagogical and supporting staff, which was important and necessary for the future physicians at all times. Thus, the Johns Hopkins University School of Medicine provided students the opportunity to work with rare library funds and to analyze scientific literature during weekly student meetings. One of the most popular meetings among students and academic staff was the Physiological Journal Club with Professor Howell. Furthermore, the Medical School established its own academic journal «The Journal of Experimental Medicine» in 1896. Note that the journal exists in the twenties of the 21st century. Moreover, the article covers other positive organizational and pedagogical principles of Johns Hopkins University School of Medicine in the 1890s. On the prospects of further scientific research, we are going to highlight activity of Johns Hopkins University School of Medicine in the 20th century and in the twenties of the 21st century with the purpose to reconsider and introduce a positive experience in Ukrainian higher medical education.
Johns Hopkins (1795-1873) and his role in developing American medical education of the 19th century
Keywords: американська медична освіта; медична школа університету Джонза Гопкінза; передумови створення; заповіт Дж. Гопкінза; американський жіночий рух; відкриття; діяльність; жіноча медична освіта; American medical education; Johns Hopkins University School of Medicine; preconditions of establishing; J. Hopkins’ will; American feminist movement; opening; activity; female medical education